Health promotion in Malaysia. - Gyanchand Rampal, Lekhraj Rampal; Lee, Shiu Hung (Chung Chi College, The Chinese University of Hong Kong, 2012)
The infrastructure, services for health promotion is currently mainly funded by Ministry of Health (MOH). The MOH is the main provider for health promotion services both in urban and rural communities with institutions of higher learning, private hospitals, and general medical practitioners playing a complimentary role. The Ministries of Education (MOEd), Ministries of Transport, non-government organizations (NGOs), community and private sector also carry out health promotion activities. Doctors, medical assistants, nurses, and health inspectors (assistant environment health officers) from the Ministry of Health have played a key role as health promoters at the hospital and community level as the primary agents of change. In the hospital setting, patient education services include bed side teaching, counseling, and dedicated classes for patient and care takers. The challengers faced are that many of the NGOs are not health related and don’t have the capacity to deliver health promotion. A lot of capacity building need to be in place. The Tak Nak (SAY NO TO SMOKING) Campaign is aimed to increase awareness of the hazards of tobacco use and second hand smoke, and at the non smoker not to start smoking. The impact of the Tak Nak Campaign and Tobacco control activities is shown by the decline in the prevalence of smoking from 47.2% in 2004 [9] to 46.4% in 2006 [4] for the males and from 2.7 % in 2004[9] to 1.6 % [4] in 2006 for the females. Since 1992, mass media and print media has been used to encourage people to have a balanced diet and to reduce their intake of unhealthy food. Media campaign with the aim of increasing physical activity has been one of the major health education and promotion activities by the Ministry of Health. The Role of NGOs in Health Promotion in Malaysia is highlighted.